Simultaneous phosphorus removal and adsorbents recovery with Ca-PAC assisted adsorption dynamic membrane system: Removal performance and influencing factors. (15th January 2023) - Li, Lucheng; Zhu, Zehua; Shi, Jingxin; Li, Zhenxuan; Zuo, Xiaojun
Abstract: Ca(OH)2 treated powdered activated carbon (Ca-PAC) assisted adsorption dynamic membrane system was proposed for simultaneous phosphorus adsorption and micrometer scale adsorbent recovery. In Ca-PAC assisted adsorption dynamic membrane system, adsorption and dynamic membrane separation acted as the key roles for pollutants removal. At first, the effect of Ca(OH)2 concentration in Ca-PAC preparation was evaluated. Phosphorus removal rate increased from 3.79% to 98.01% when added Ca(OH)2 concentration was increased from 0 to 2 M in PAC treatment. Effect of initial phosphorus concentration, reaction temperature, and solution pH on phosphorus removal with Ca-PAC was explored in this study. And then, adsorption isotherms, adsorption kinetics, SEM, XRD, and FTIR were conducted to explain the phosphorus adsorption. Ligand exchange between hydroxyl on Ca-PAC and phosphate was confirmed to be the main phosphorus removal mechanism, with little Ca–P precipitation verified in X-ray diffraction (XRD) analysis. At last, integrated adsorption dynamic membrane system was operated with Ca-PAC, showing more than 90% phosphorus adsorbed in 1 min and 63.25%–87.65% micrometer scale Ca-PAC recovered. Overall, adsorption-dynamic membrane system presents to be stable and applicable in deep phosphorus removal and micrometer scale adsorbent recovery, which presents a new route for micrometer scale adsorbent application and recovery in actual surface water and wastewater treatment. Graphical abstract: Image 1 Highlights: A sustainable Ca-PAC based adsorption dynamic membrane system was proposed. Simultaneous phosphorus removal and micrometer scale Ca-PAC recovery were achieved. Micrometer scale Ca-PAC was used as formation material of dynamic membrane.